2018
DOI: 10.1016/j.scitotenv.2017.08.102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of airborne ammonium and nitrate pollution strongly differ in peat bogs, but symbiotic nitrogen fixation remains unaffected

Abstract: Pristine bogs, peatlands in which vegetation is exclusively fed by rainwater (ombrotrophic), typically have a low atmospheric deposition of reactive nitrogen (N) (<0.5kghay). An important additional N source is N fixation by symbiotic microorganisms (diazotrophs) in peat and mosses. Although the effects of increased total airborne N by anthropogenic emissions on bog vegetation are well documented, the important question remains how different N forms (ammonium, NH, versus nitrate, NO) affect N cycling, as their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 86 publications
2
27
0
Order By: Relevance
“…In addition, we supplied P to the mesocosms via injection just below the moss surface (capitula). Although this way of P-fertilization is dissimilar to other studies (Limpens et al 2004;Fritz et al 2012;van den Elzen et al 2017), it resembles the way increased P fluxes enter peat ecosystems in reality. P-fertilization is in most studies sprinkled on top of the mosses or added in the inflowing surface water.…”
Section: Fertilization Effectsmentioning
confidence: 57%
See 4 more Smart Citations
“…In addition, we supplied P to the mesocosms via injection just below the moss surface (capitula). Although this way of P-fertilization is dissimilar to other studies (Limpens et al 2004;Fritz et al 2012;van den Elzen et al 2017), it resembles the way increased P fluxes enter peat ecosystems in reality. P-fertilization is in most studies sprinkled on top of the mosses or added in the inflowing surface water.…”
Section: Fertilization Effectsmentioning
confidence: 57%
“…For leguminous plant species it has recently been reported that the plants modulate their carbon allocation to symbiotic nitrogen-fixing Rhizobia in response to both light an N availability (Friel and Friesen 2019). For N 2 fixation associated with Sphagnum, it has been observed before that N 2 fixation rates are highest under illuminated conditions (Larmola et al 2014;van den Elzen et al 2017). This is true even though N 2 fixation is inhibited by presence of O 2 (Vitousek et al 2013).…”
Section: Light As a Key Driver Of N 2 Fixationmentioning
confidence: 99%
See 3 more Smart Citations